Off-resonance magnetic resonance angiography improves visualization of in-stent lumen in peripheral nitinol stents compared to conventional T1-weighted acquisitions: an in vitro comparison study - Gitsioudis, Gitsios; Fortner, Philipp; Stuber, Matthias; Missiou, Anna; André, Florian; Müller, Oliver J.; Katus, Hugo; Korosoglou, Grigorios (The international journal of cardiovascular imaging, 2016)
To compare the value of inversion recovery with on-resonant water suppression (IRON) to conventional T1-weighted (T1w) MRA and computed tomography angiography (CTA) for visualization of peripheral nitinol stents. We visualized 14 different peripheral nitinol stents in vitro both using Gadolinium (Gd) and ultrasmall superparamagnetic iron nanoparticles (USPIOs) for conventional T1w and IRON-MRA using clinical grade 1.5T MR scanner and iodinated contrast material for CTA using a 256-slice CT scanner. Parameter assessment included signal- and contrast-to-noise ratio (S/CNR), relative in-stent signal and artificial lumen narrowing. X-ray angiography served as gold standard for diameter assessment. Gd-enhanced IRON-MRA exhibited highest in-stent SNR and CNR values compared to conventional T1w MRA (IRON (Gd/USPIO): SNR = 30 ± 3/21 ± 2, CNR = 23 ± 2/14 ± 1; T1w: SNR = 16 ± 1/14 ± 2, CNR = 12 ± 1/10 ± 1, all p < 0.05). Furthermore, IRON-MRA achieved highest relative in-stent signal both using Gd and USPIO (IRON (Gd/USPIO): 121 ± 8 %/103 ± 6 %; T1w: 73 ± 2 %/66 ± 4 %; CTA: 84 ± 6 %, all p < 0.05). However, artificial lumen narrowing appeared similar in all imaging protocols (IRON (Gd/USPIO): 21 ± 3 %/21 ± 2 %; T1w: 16 ± 4 %/17 ± 3 %; CTA: 19 ± 2 %, all p = NS). Finally, IRON-MRA provided improvement of the in-stent lumen visualization with an ‘open-close-open’ design, which revealed a complete in-stent signal loss in T1w MRA. IRON-MRA improves in-stent visualization in vitro compared to conventional T1w MRA and CTA. In light of the in vitro results with Gd-enhanced IRON-MRA, the clinical implementation of such an approach appears promising.
Gesehen am 12.06.2020